Effect of dispersion of gold nanoparticles on the properties and alignment of liquid crystalline copper phthalocyanine films. (February 2016) - Basova, Tamara V.; Parkhomenko, Roman G.; Polyakov, Maxim; Gürek, Ayşe Gül; Atilla, Devrim; Yuksel, Fatma; Ryabchikova, Elena I.; Kadem, Burak Y.; Hassan, Aseel K.
Abstract: The inclusion of hexadecylamine capped gold nanoparticles (AuNPs) into the ordered matrix of hexagonal columnar mesophase of copper phthalocyanine (CuPc) has been investigated. The effects of AuNPs on the liquid crystalline behaviour, optical and electrical properties of CuPc films is investigated by different physical methods. The molecules orientation in the films of CuPc and its composites with AuNPs, deposited on the surface of one substrate and between two electrodes, is studied by polarized Raman spectroscopy and polarized microscopy. It has been shown that thin films of the composites confined between ITO and Al electrodes are characterized by homeotropic alignment while no homeotropic alignment was observed in films deposited on ITO substrate with air constituting the upper interface. The I(V) dependences for the films confined between ITO and Al electrodes were measured. Appreciable enhancement of the DC conductivity is observed in the case of composites containing gold nanoparticles. Graphical abstract: Highlights: Properties of copper phthalocyanine with hexadecylamine capped gold nanoparticles have been investigated. Structural features and orientation of composite films have been investigated. Gold nanoparticles does not alter the mesophase structure. Addition of AuNP leads to a significant increase in the electronic conduction.